2014
DOI: 10.1080/0161956x.2014.897104
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Supports for Young People: What Do Existing Supports Reveal About the Recovery Environment?

Abstract: This article seeks to address how our understanding of the recovery process and resulting supports can be made more comprehensive: how can links from treatment to home to school to communities be made so that there are fewer and fewer recovery gaps for adolescents? Using the ecology of recovery model developed by White (2009) as the impetus for such a review, the article discusses the challenges inherent within adolescent substance abuse recovery, factors impacting successful recovery, and programs addressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Despite the existence of adolescent-specific treatment, continuing care programs, and schools for adolescents in recovery (Fisher, 2014; Moberg & Finch, 2007), academic definitions of recovery differ. Therefore, it remains important to understand how practitioners, who are in daily contact with adolescents in treatment or recovery support services, view and discuss success in recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the existence of adolescent-specific treatment, continuing care programs, and schools for adolescents in recovery (Fisher, 2014; Moberg & Finch, 2007), academic definitions of recovery differ. Therefore, it remains important to understand how practitioners, who are in daily contact with adolescents in treatment or recovery support services, view and discuss success in recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, today there are adolescent treatment and continuing care programs and even schools and collegiate recovery communities for youth in recovery (Fisher, 2014; Moberg & Finch, 2007). For example, recovery high schools (RHS) are schools meeting state requirements for awarding a secondary diploma with a primary purpose of educating youth in recovery (Association of Recovery Schools, 2016, p. 20).…”
Section: Introductionmentioning
confidence: 99%
“…This pilot study recruited 80 youth to participate in an aftercare project called Project Educating and Supporting inQuisitive Youth in Recovery (ESQYIR) between 2012 and 2014 from both outpatient and residential community-based treatment programs located throughout diverse areas of Southern California. Inclusion criteria included being a youth defined broadly as adolescents (12)(13)(14)(15)(16)(17) or transitional age youth (TAY: 18-25); completing treatment, which consisted of relapse prevention/cognitive behavioral groups ranging from 12 to 16 weeks; and owning a mobile phone with SMS texting capabilities. Exclusion criteria included not obtaining parental consent (if adolescents); not willing to comply with the aftercare study procedures; and any psychological/medical conditions that warranted further primary treatment.…”
Section: Participantsmentioning
confidence: 99%
“…14,15 Research has shown favorable outcomes resulting from the use of such alternative aftercare approaches with young people, including reduced substance use and improved psychosocial functioning post-treatment 16 ; however, participation in aftercare programs that support recovery for young people continue to pose challenges for the treatment field. 6,9,17 Exploring recovery needs among young people in treatment for substance use disorders, Gonzales et al 18 found that a majority view recovery as improving one's behavioral lifestyle, asserting personal control, and engaging in wellness related behavioral changes. The wellness concept has been commonly applied in disease self-management extended care interventions within the healthcare field to help individuals with complex conditions engage in lifestyle change and improve symptoms by promoting self-responsibility for behavior/health.…”
Section: Introductionmentioning
confidence: 99%
“…Existing sources of post-treatment recovery support for adolescents are marked by varying levels of empirical evidence and fall into one of two categories: professionally-directed "formal aftercare or continuing care services" or peer-based support provided within "recovery communities" (Fisher, 2014). Formal continuing care is typically offered in outpatient clinics to clients who complete their acute episode of care.…”
Section: Introductionmentioning
confidence: 99%